A Clinicopathological Evaluation of Malignancies of Maxilla- Ethmoid Complex - Kumari Radha M. N; Vijayalakshmi R (Asian Journal of Medical Research, 2018)
Background: Aim: Assessment of malignancies of maxillo- ethmoid complex. Materials and Methods: Eighty- four malignancies of maxillo- ethmoid complex in either gender was enrolled. Investigations like Punch biopsy and excision biopsy, were done and the pathological subtype of the tumor was noted. Appropriate treatment modality like surgery, radiotherapy and chemotherapy, individually or in combination, were instituted for each case. Cases were followed up at 1, 3, 6 months and 1 year following treatment. Results: Common site was in ethmoid sinus in 36 in maxillary sinus 30, in nasal cavity 14. Malignancies found to be SCC in 42, adenocarcinoma in18, adenoid cystic carcinoma in 7, Esthisioneuroblastoma 5, mucosal melanoma in 4, osteosarcoma in 2, and lymphoma in 4 cases. Treatment given was chemotherapy in 34, surgery in 7, radiotherapy in 3, surgery+ radiotherapy in 26, surgery+ chemotherapy in 4, radiotherapy+ chemotherapy in 4 and surgery+ radiotherapy+ chemotherapy in 6 patients. Conclusion: In most of cases, ethmoid sinus was involved and most common malignancies was squamous cell carcinoma.